2019 IEEE International Conference on Software Architecture Companion (ICSA-C) 2019
DOI: 10.1109/icsa-c.2019.00016
|View full text |Cite
|
Sign up to set email alerts
|

Microservice Architectures for Advanced Driver Assistance Systems: A Case-Study

Abstract: The technological advancements of recent years have steadily increased the complexity of vehicle-internal software systems, and the ongoing development towards autonomous driving will further aggravate this situation. This is leading to a level of complexity that is pushing the limits of existing vehicle software architectures and system designs. By changing the software structure to a service-based architecture, companies in other domains successfully managed the rising complexity and created a more agile and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
0
13
0
6
Order By: Relevance
“…A recent trend in automotive architectures is the migration to service-oriented architectures [29,40,41] to allow for more flexible and faster development and deployment. In a recent case study, we have shown how an advanced driver assistance function can be migrated to a microservice architecture [30]. The definition of modular services may well support our proposed refactoring approach.…”
Section: Related Workmentioning
confidence: 79%
See 1 more Smart Citation
“…A recent trend in automotive architectures is the migration to service-oriented architectures [29,40,41] to allow for more flexible and faster development and deployment. In a recent case study, we have shown how an advanced driver assistance function can be migrated to a microservice architecture [30]. The definition of modular services may well support our proposed refactoring approach.…”
Section: Related Workmentioning
confidence: 79%
“…The most prominent example of a layered architecture for automotive software is probably AUTOSAR [28], which decouples application software components from base software components within an ECU. However, also within the application software, there is a trend towards structuring the application software components with respect to different dedications (e.g., sensor fusion, controllers, service functionality) [29,30]. Figure 3 shows an example of an application software component architecture that has a dedicated platform component layer (PCL).…”
Section: Layered Component Architectures and Communal Componentsmentioning
confidence: 99%
“…As an example, the RACE approach [89] was initialised in 2012. More recently, Lotz et al [61] published one approach that relies on a run-time environment for microservices. In this work, we are using the SOME/IP as the communication protocol.…”
Section: Implementation-related Contributionsmentioning
confidence: 99%
“…Several solutions for this problem have been suggested, all with their specific advantages or disadvantages: Applying the API Gateway pattern [28], as recommended by Taibi and Lenarduzzi [27], is a possible way of decoupling the system, switching to an asynchronous communication model is another [7,19]. While the first approach reduces the coupling, it bears the risk of creating a single point of failure in the system [15]. Worse, in this solution there is still a cycle in the system, but just via the API gateway.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors (see e.g. [15,33]) suggest that the only effective way to resolve these domain-based communication cycles is redesigning the architecture on the domain level. However, for this, the cyclic connections first have to be identified, which is not always a trivial task, considering the polyglot nature of microservice implementations [26].…”
Section: Introductionmentioning
confidence: 99%